Association of demographic characteristics and clinical symptoms with prostate volume grade on transabdominal ultrasound in patients with benign prostatic hyperplasia - Dewa Komang Agung Hersya Paritranaya Dinata; Ni Made Putri Suastari; Ni Made Widya Mahayani (Poltekkes Kemenkes Bandung, 2026)
Background: Benign Prostatic Hyperplasia (BPH) is a degenerative prostate disease that causes Lower Urinary Tract Symptoms (LUTS) in older men. Demographic characteristics and clinical symptoms of LUTS based on IPSS score, are thought to be associated with prostate volume, which is influenced by individual factors and clinical manifestations. Ultrasound is an important test for assessing prostate enlargement in BPH. Objective: This study aimed to analyze the relationship between demographic characteristics and clinical symptoms and the degree of prostate volume as determined by transabdominal ultrasound in patients with BPH. Methods: This study was an analytical observational study with a cross-sectional design, using total sampling on 71 respondents. Using both primary and secondary data. Data analysis was performed using univariate tests and bivariate tests (Fisher’s Exact test). Results: The study revealed significant associations between demographic characteristics and clinical symptoms and prostate volume. There is an association between educational level and prostate volume (p<0.001); occupation is associated with prostate volume (p<0.002); there is an association between comorbidities and prostate volume (p<0.028); and there is an association between the severity of LUTS symptoms as measured by the IPSS and prostate volume (p<0.001). Conclusion: This study found a significant association between demographic characteristics and clinical symptoms and the degree of prostate volume as determined by ultrasound. As age increases and the severity of LUTS symptoms worsens, prostate volume tends to be larger. Educational level, occupation, and comorbidities are also associated with larger prostate volume.